Effect of IVF failure on quality of life and emotional status in infertile couples. (November 2016) - Karaca, Nilay; Karabulut, Aysun; Ozkan, Sevgi; Aktun, Hale; Orengul, Fatma; Yilmaz, Rabiye; Ates, Seda; Batmaz, Gonca
Abstract: Objective: To investigate the effect of a previous IVF failure on the quality of life and emotional distress, in couples undergoing IVF treatment. Experiencing IVF failure might cause differences on the anxiety-depression and quality of life scores of the couples, compared to the ones who were undergoing IVF treatment for the first time. Study design: This study included 64 couples who had previously experienced at least one IVF failure (Group 1) and 56 couples without history of IVF failure (Group 2) in a private Assisted Reproductive Center, Istanbul, Turkey. A sociodemographic data form, the FertiQoL International and Hospital Anxiety (HAD-A) and Depression scale (HAD-D) for evaluating the status of distress, were administered for the study. Result(s): FertiQoL scores were compared between the groups, the environment scale of the quality of life in treatment section was found to be significantly higher in Group 1 compared with Group 2 (p = 0.009). The HAD-A and HAD-D scores did not differ significantly between the groups. Group-variables were investigated using multilevel analysis, the infertility duration and income level were found to have an effect on the subscales of quality of life (p = 0.009 and p = 0.001 respectively) in Group 2. Depression scores were higher in couples with infertility duration of below five years in Group 1 and Group 2 compared to couples with infertility duration of five years or above (MANOVA analysis). The level of education was found to affect the scores of HAD-D in Group 2, but not in Group 1 (p = 0.011). The score of HAD-D was significantly affected by the family type only in Group 2 (p = 0.009); the depression score of the couples living with a nuclear family was found to be higher compared with the couples living in a traditional family (p = 0.021). Conclusion(s): Fertility-specific quality of life scores reveals better results regarding the orientation to the treatment environment in the couples with a previous IVF failure, compared to first IVF cycle couples. Treatment failure does not elevate the level of anxiety, while the effect on depression scores changes according to duration of infertility.